Century 21 Computer keyboarding - Hoggatt, Jack P.
Century 21 Computer Keyboarding gives you what you are looking for in a one semester course on new key learning, document formatting, and word processing. This text is a combination of 50 lessons of key learning/ technique mastery and 25 lessons on word processing/document formatting